Comparative study of mandibular glands of Melipona bicolor queens obtained from polygynic and monogynic colonies - Vitti, LFG; Abdalla, Fábio Camargo [UNESP]; De Moraes, RLMS (Inst Histol Embriol-conicet, 2005)
The aim of the present study was analyze, by histological and morphometrical studies, mandibular glands of Melipona bicolor queens collected from monogynic and polygynic colonies and compare their level of development. The results showed that the glands of physogastric queens from monogynic colony present a higher level of activity in relation to the queens of polygynic colonies; this is explained by the fact that just a unique queen controls the monogynic colony. In the polygynic colonies, the queens may divide such control to each other.
Keywords: Melipona bicolor; mandibular gland; morphology; polygynic colonies